Pengaruh Kascing dan Mikoriza terhadap Pertumbuhan dan Hasil Tribulus terrestris - Samanhudi, Samanhudi (Jurnal Agrotek Indonesia, 2017)
Tribulus terrestris is one of the medicinal plants consumed in Indonesia that contain a variety of components. Saponins in Tribulus is an active component that can eliminate sexual dysfunction, improve erection function, protect the myocardium against ischemia/reperfusion injury and hypertension, and coronary heart disease. Various benefits contained in the Tribulus resulted in the tremendous opportunity to develop Tribulus in Indonesia. The reality in Indonesia is still very few farmers who develop Tribulus as the mainstay in planting, so that the yield and production of these plant are needed to meet market demand in Indonesia. It has prompted the need for proper cultivation and in accordance with the use of vermicompost fertilizer and mycorrhiza. This research aims to determine the effect of a dose of vermicompost and mycorrhiza on growth and yield of Tribulus. This research was conducted at the experimental farm of Faculty of Agriculture, Universitas Sebelas Maret in the village of Sukosari, Jumantono, Karanganyar. The research was conducted for three months, in June until August 2016. The design used in this research is a Completely Randomized Block Design (CRBD) arranged as factorial, consists of two factors of treatment with three experimental blocks. The first treatment factors that dose of vermicompost fertilizer consists of four levels: 0, 10, 20, 30 tonha-1. The second treatment factor is the dose of mycorrhiza consists of three levels: 0, 50, 100 sporesplant-1. The data were analyzed by F test or analysis of variants (Anova) continued with Duncan Multiple Range Test (DMRT) level of 5%. Mycorrhiza treatment dose of 100 sporesplant-1 gave the highest yield on the weight of the wet stover (844.63 g), time of the flowers appear (7 DAP), the number of branches (8 branchesplant-1), sum of fruit (627 fruits), and seed number (3,135 seeds). Mycorrhiza treatment dose of 50 sporesplant-1 gives the highest yield on plant height (167.8 cm). Meanwhile, vermicompost fertilizer treatment dose of 20 tonha-1 gives the best results on root volume (38.31 cm3). Keywords: medicinal plant, mycorrhiza, Tribulus terrestris, vermicompost.